Lysine, Lysine-Rich, Serine, and Serine-Rich Proteins: Link Between Metabolism, Development, and Abiotic Stress Tolerance and the Role of ncRNAs in Their Regulation - KAVI KISHOR, POLAVARAPU B.; Suravajhala, Renuka; Guddimalli, Rajasheker; Marka, Nagaraju; Kavya Shridhar, K; Divya, D; Scinthia, K P.; Divya, Kummari; Doma, Madhavi; Edupuganti, Sujatha; Suravajhala, Prashanth N.; Polavarapu, Rathnagiri (Frontiers in Plant Science, 2020)
Lysine (Lys) is indispensable nutritionally, and its levels in plants are modulated by both transcriptional and post-transcriptional control during plant ontogeny. Animal glutamate receptor homologues have been detected in plants, which may participate in several plant processes through the Lys catabolic products. Interestingly, a connection between Lys and serotonin metabolism has been established recently in rice. 2-Aminoadipate, a catabolic product of Lys appears to play a critical role between serotonin accumulation and the colour of rice endosperm/grain. It has also been shown that expression of some lysine-methylated proteins and genes encoding lysine-methyltransferases (KMTs) are regulated by cadmium even as it is known that Lys biosynthesis and its degradation are modulated by novel mechanisms. Three complex pathways co-exist in plants for serine (Ser) biosynthesis, and the relative preponderance of each pathway in relation to plant development or abiotic stress tolerance are being unfolded slowly. But the phosphorylated pathway of L-Ser biosynthesis (PPSB) appears to play critical roles, and is essential in plant metabolism and development. Ser, which participates indirectly in purine and pyrimidine biosynthesis plays a pivotal role in plant metabolism and signaling. Also, L-Ser has been implicated in plant responses to both biotic and abiotic stresses. A large body of information implicates Lys-rich and serine/arginine-rich (SR) proteins in a very wide array of abiotic stresses. Interestingly, a link exists between Lys-rich K-segment and stress tolerance levels. It is of interest to note that abiotic stresses largely influence the expression patterns of SR proteins and also the alternative splicing (AS) patterns. We have checked if any lncRNAs form a cohort of differentially expressed genes from the publicly available PPSB, sequence read archives of NCBI GenBank. Finally, we discuss the link between Lys and Ser synthesis, catabolism, Lys- and SR proteins during plant development and their myriad roles in response to abiotic stresses.